The Influence of Work Environment and Organizational Culture on Organizational Commitment in Mediation by Work Stress at Bank Indonesia Representative Office in North Sumatra Province - Andi Fajar Al Hadi; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study aims to see the Influence of Work Environment and Organizational Culture on Organizational Commitment in Mediation by Work Stress at the Bank Indonesia Representative Office in North Sumatra Province. Bank Indonesia is an independent state institution tasked with considering economic policies in Indonesia. In addition to these functions, Bank Indonesia has an internal scope of work that is under the management of the Internal Management field. One of the sections under the internal division of Bank Indonesia is the Human Resources (HR) section. Bank Indonesia's human resources have several tasks in managing employees, one of which is the processing of employee health data. The results of this study are as follows: Organizational Culture has a positive and insignificant effect on Organizational Commitment with the original sample value of 0.129 and p values of 0.205. Organizational Culture had a negative and significant effect on Work Stress with a sample value of -0.498 and p values of 0.000. The Work Environment had a non-significant positive effect on Organizational Commitment with the original sample value of 0.483 and p values of 0.002. The Work Environment had a negative and significant effect on Work Stress with the original sample value of -0.476 and p values of 0.000. Work Stress had a negative and significant effect on Organizational Commitment with the original sample value of -0.107 and p values of 0.308. Organizational Culture has a positive and significant effect on Organizational Commitment through Work Stress indirectly with the original sample value of 0.053 and p values of 0.315. The Work Environment had a positive and insignificant effect on Organizational Commitment through Work Stress with the original sample value of 0.051 and p values of 0.306.